An effective islanding detection method for photovoltaic grid connected inverter / Ku Nurul Edhura Ku Ahamad - Ku Nurul Edhura , Ku Ahamad (2013)
Presently, available international standard related to anti-islanding requirements on medium and low grid connected system required that voltage utility distribution network should be automatically disconnected from the distribution grid when the circuit breaker supplying the feeder connected to the distribution generation trips. Islanding is undesired because it may endanger maintenance service workers and damage load equipment through unsynchronized re-closure. In principle, the main idea of islanding is monitoring the changes in the output parameter of the inverters or other system parameters in indicating islanding. This thesis presented a low cost and effective passive anti-islanding detection method for single-phase photovoltaic grid-connected inverters. An analog circuit for over/under voltage protection is developed to ensure fast detection and no delay to system. An under- /over frequency circuit is also developed, for accurate and fast frequency detection with minimal external components. A new algorithm is developed in a low cost PIC18F4550. An improved disconnection time in the proposed method compared with that in the previously developed method is an attractive solution for single phase grid connected inverters. The low cost, effective and minimal external component count are the advantages. A prototype is developed and tested to demonstrate the performance and feasibility of the proposed method. The test was conducted on different combination of resistive, capacitive and inductive loads. The experiment results verified that the proposed anti-islanding detection method is able to detect islanding operation effectively under various load types, inverter output powers and quality factors.